2021
DOI: 10.1136/bmjopen-2021-054959
|View full text |Cite
|
Sign up to set email alerts
|

Early-term birth and its association with universal two-child policy: a national cross-sectional study in China

Abstract: ObjectiveTo describe the epidemiology of early-term birth (ETB) at the national level in China, and explore the association and mediating factors between ETB and policy between universal two-child policy and ETB, so as to explain the potential reason for such a relationship and provide evidence for future ETB interventions in the era of the new birth control policy.DesignCross-sectional study.ParticipantsThe cross-sectional study used data from China Labour and Delivery Survey between 2015 and 2016. A total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Recently, a signi cantly increased risk of preterm birth was reported in the TCP period. Zhang [13] observed that more pregnant women, who delivered before 37 gestational weeks suffered from complications, including preeclampsia, oligohydramnios and placenta previa, during the TCP period. In contrast to previous studies [7] , we found no signi cant difference in the risk of preterm birth in pregnancies among women with AMA during the TCP period.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a signi cantly increased risk of preterm birth was reported in the TCP period. Zhang [13] observed that more pregnant women, who delivered before 37 gestational weeks suffered from complications, including preeclampsia, oligohydramnios and placenta previa, during the TCP period. In contrast to previous studies [7] , we found no signi cant difference in the risk of preterm birth in pregnancies among women with AMA during the TCP period.…”
Section: Discussionmentioning
confidence: 99%
“…After the announcement in October 2015, the universal two‐child policy has been associated with a rise in births and that women giving birth have been more likely to be aged 35 years and over 9 . Whether the universal two–child policy would cause adverse outcomes has not been clear, 9,10 though, a national cross‐sectional study in China by Zhang et al showed that ETB was found to be more likely to happen under the universal two‐child policy, 11 and a wide range of adverse pregnancy outcomes have been proved to be associated with women of advanced maternal age including ETB and low birth weight and macrosomia which make these newborns more vulnerable to pathogen infections due to the less developmental immature immune system (e.g., lower level of immunoglobulins, antimicrobial peptides and proteins, and complement proteins) responsible for eliminating the pathogens 12,24–26 . Besides, Yuan et al reported that the incidence of obstetric infection increased nearly twice after the universal two‐child policy, which might also increase the risk of infection of the newborns 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Since the announcement in October 2015 and implementation in January 2016 in China, the universal two‐child policy has been associated with a rise in births and that women giving birth have been more likely to be aged 35 years and over 9 . Whether the universal two–child policy would cause adverse outcomes remained unclear, 9,10 however, one study has reported an association between the universal two‐child policy and early‐term birth (ETB) 11 . ETB could lead to immunocompromise due to the lower levels of soluble factors in premature children such as immunoglobulins, antimicrobial peptides, and proteins and complement proteins, and so forth which are responsible for eliminating the pathogens 12 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations